Integration of Ethnochemical Concepts in Redox Reaction Learning - Daulay, Rabiah Afifah; Syafitri, Amelia; Aulianti, Dita; Azhari, Serlina Wati; Simaremare, Happy G. Maritoma (LAVOISIER: Chemistry Education Journal, 2025)
Learning about redox reactions is often considered difficult by students, especially because of its abstract nature and lack of connection to everyday life. In this case, an ethnochemical approach can be an effective solution to connect chemical concepts with local culture, so that students' understanding can be improved. This study aims to analyze how the integration of ethnochemical concepts in learning redox reactions can be implemented. The method used in this study is qualitative with a descriptive approach, through a literature study that discusses various academic references. The results of the study indicate that the application of ethnochemistry in learning redox reactions can be done through various cultural examples, such as the fermentation process of tape and tempeh, the use of natural dye oxidation in batik coloring, and metal processing in traditional crafts. This integration not only improves students' understanding of chemical concepts but also enriches their insights into local wisdom and environmental sustainability. With a more contextual learning approach, students can more easily relate theory to real practice. This in turn can increase their interest and understanding of chemistry.